1999
DOI: 10.1046/j.1524-475x.1999.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of markers of collagen remodeling in venous ulcers

Abstract: A 25 patient study was conducted into the relationship between markers of collagen metabolism in venous ulcer exudates and healing status, and their prognostic value in predicting healing performance. Wounds were sampled on at least 5 occasions over 12 months, the frequencies of which were determined by the need for clinic attendance. Specimens were taken from several sites on each ulcer using sterile preweighed filters. Wound margins were traced and sites recorded for each collection. Sample sites were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 17 publications
2
92
0
Order By: Relevance
“…Higher levels in unhealed patients indicate over-activity of MMP2, resulting in greater breakdown of the extracellular matrix, thus hindering healing [17]. Indeed, increased expression and/or activity of MMPs, including MMP2, has previously been observed in diabetic foot ulcers and venous ulcers, and related to healing status [18]. Our findings are therefore consistent with the notion that increased levels of MMP2 may contribute to the chronicity of diabetic foot ulcers.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Higher levels in unhealed patients indicate over-activity of MMP2, resulting in greater breakdown of the extracellular matrix, thus hindering healing [17]. Indeed, increased expression and/or activity of MMPs, including MMP2, has previously been observed in diabetic foot ulcers and venous ulcers, and related to healing status [18]. Our findings are therefore consistent with the notion that increased levels of MMP2 may contribute to the chronicity of diabetic foot ulcers.…”
Section: Discussionsupporting
confidence: 91%
“…Sterile, preweighed filter paper was applied to the wound to absorb fluid using methods described previously [18], and then reweighed and stored at −80°C until processing. Levels of MMPs were normalised to the mass of fluid collected.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This neodermal tissue initially consists of type III and V collagens, fibronectin and proteoglycans, which are slowly replaced by collagen I (the most abundant collagen in uninjured dermis), itself gradually remodeled as the resultant scar tissue matures. In chronic, non-healing wounds, these processes are disturbed and excessive tissue breakdown results in the failure to accumulate sufficient amounts of several key matrix components as a result of both decreased rates of protein biosynthesis 33 and greatly increased proteolytic activity. 34 Intriguingly, male gender is the primary factor predisposing to chronic wound healing states in humans, 23 and our recent studies have demonstrated that androgens impair healing in mouse and human models.…”
Section: Discussionmentioning
confidence: 99%